THE INFLUENCE OF GROUP CONFORMITY TO BEHAVIOR DEVIATE STUDENT - Zaman, Khosim Nur (Bisma The Journal of Counseling, 2020)
Some problems that occur in students related to conformity or join in related to the influence of groups or other parties, conformity related to high risk relationships, such as deviating and discussing the law, this research seeks to find an acceptable fix in a group that is categorized as an appropriate action (part of it). the purpose of this study is to determine the relationship of group conformity to the distorted discussion of students looking at the forms of group conformity in students, how to deviate obtained from conformity including bullying, extortion, smoking, beating and canceled cheating during exams, this study uses quantitative research methods in terms of the level of explanation, this study also uses associative forms of causal relations with other objectives to apply the process of confrement to group variables. There are independent and variable variables el in this study are: 1) group conformity 2) deviant motivation, data collection techniques using questionnaires, data collection methods are done by giving separate questions, or asking for help, respondents respond, loosen in the form of data, data analysis of this study is a technique simple linear regression analysis with the help of the SPSS program. based on the results of the analysis of data techniques with the simple linear regression analysis method the conformity to complaints contributes to 0.069 at the significance level (p <0.05). between group conformity to deviate, in other words the hypothesis is accepted